[Joint Statement of the German Radiological Society and the German Respiratory Society on a Quality-Assured Early Detection Program for Lung Cancer with Low-dose CT]. - Herth, Felix J. F.; Reinmuth, N.; Wormanns, D.; Antoch, G.; Biederer, J.; Vogel-Claussen, Jens; Kauczor, H-U; Pfeifer, M.; Bauer, T. T.; Randerath, W. J.; Koehnlein, T.; Rabe, K. F.; et al. (Pneumologie, 2019)
Substantial new data on early detection of lung cancer with low-dose CT has become available since the last joint statement of the German Roentgenological Society and the German Respiratory Society was published in 2011. The German S3 guideline on lung cancer was revised in 2018 and now contains a weak recommendation towards early detection of lung cancer with low-dose CT in a quality-assured early detection program. These new developments required a repositioning of the involved professional societies. This present joint statement describes main features of a quality-assured program for early detection of lung cancer with low-dose CT in Germany.
EVALuna2:212805